Analisis kandungan siklamat, metanil yellow dan rhodamin b pada makanan dan minuman di Cikarang - Nurpratama, Widya Lestari; Kinayungan, Utami Putri; Alamsah, Deni; Sanjaya, Dandi; Asmi, Nur Fauzia; Heryanda, Mahfuzhoh Fadillah (Poltekkes Kemenkes Aceh, 2025)
Background: Food Additives (BTP) are substances that are intentionally added to improve food quality without providing nutritional value, examples of BTP are artificial sweeteners and dyes such as cyclamate, metanil yellow, and rhodamin B which focus on identifying their content in food and beverages in Cikarang. The research was conducted in Cikarang, which is an area with high population density and rapid economic activity.Objectives: Analyzing the content of cyclamate, metanil yellow, and rhodamine B in food and beverages in Cikarang.Methods: The experimental research design used accidental sampling with a sample size of 20 for the cyclamate test, 15 for the rhodamine B and methanyl yellow tests. Sampling was tested directly with the Test Kit brand labstest for the cyclamate, metanil yellow, and rhodamine B tests carried out at the Integrated Chemistry Laboratory at Suherman Medika University. Data collection was carried out in April 2025. Data analysis was carried out descriptively, namely showing the percentage of food and beverage content containing artificial sweeteners cyclamate and dyes metanil yellow and rhodamine B.Results: The results of the study showed that of the 20 samples tested for cyclamate, 7 samples were positive (35%) indicated by the presence of white sediment in the sample, 15 samples tested for metanil yellow did not contain metanil yellow in the sample, and 15 samples tested for rhodamine B, 2 samples were positive (13,3%) indicated by a pink color change in the sample.Conclusion: The results of the study confirmed that there were indications of the content of artificial sweeteners cyclamate, and dyes metanil yellow, and rhodamin B in several samples of food and beverages sold in the Cikarang area.